Divergent Evolutionary Patterns of NAC Transcription Factors Are Associated with Diversification and Gene Duplications in Angiosperm - Jin, Xiaoli; Ren, Jing; Nevo, Eviatar; Yin, Xuegui; Sun, Dongfa; Peng, Junhua (Frontiers in Plant Science, 2017)
NAC (NAM/ATAF/CUC) proteins constitute one of the larbiggest plant-specific transcription factor (TF) families and play have crucial important roles in diverse developmental programs during plant growth. Phylogenetic analyses have revealed both conserved and lineage-specific NAC subfamilies, among which various origins and distinct features were observed. It is reasonable to hypothesize that there should be divergent evolutionary patterns of NAC TFs both between dicots and monocots, and among NAC subfamilies, and the underlying mechanism should shed lights on how evolutionary divergence contributes to differences in establishing NAC gene subfamilies and thus impacts the distinct morphological and physiological features between dicots and grasses. However, few studies have been conducted to describe the divergent evolutionary mechanisms among NAC TFs. In this study, therefore, through genome-wide analyses of sequence and functional data in six dicot and five grass lineages, we compared the gene duplication and loss, evolutionary rate, and selective pattern among non-lineage specific NAC subfamilies, as well as those between dicots and monocots, through genome-wide analyses of sequence and functional data in six dicot and five grass lineages. The number of genes gained in the dicot lineages was much grealargter than that in the grass lineages, while fewer gene losses were observed in the grass than that in the dicots. We revealed 1) uneven constitution of Clusters of Orthologous Groups (COGs) and contrasting birth/death rates among subfamilies, and 2) two distinct evolutionary scenarios of NAC TFs between dicots and grasses. Our results demonstrated that relaxed selection, resulting from concerted gene duplications, may have permitted substitutions responsible for functional divergence of NAC genes into new lineages. Moreover, tThe underlying mechanism of distinct evolutionary fates of NAC TFs shed lights on how evolutionary divergence contributes to differences in establishing NAC gene subfamilies and thus impacts the distinct morphological and physiological features between dicots and grasses.